A historical guide to Edgar Allan Poe - Kennedy, J. Gerald (Historical guides to American authors., 2001)
Edgar Allan Poe (1809-1849), son of itinerant actors, holds a secure place in the firmament of history as America's first master of suspense. Displaying scant interest in native scenes or materials, Edgar Allan Poe seems the most un-American of American writers during the era of literarynationalism; yet he was at the same time a pragmatic magazinist, fully engaged in popular culture and intensely concerned with the ""republic of letters"" in the United States. This Historical Guide contains an introduction that considers the tensions between Poe's ""otherworldly"" settings and hishistorically